Rapid spread of African swine fever across Borneo - Olivia Z. Daniel; Sui Peng Heon; Christl A. Donnelly; Henry Bernard; C. David L. Orme; Robert M. Ewers (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
African Swine Fever (ASF) reached the island of Borneo at the end of 2020. The first mortalities were recorded in wild bearded pigs (Sus barbatus) in Sabah, north-east Borneo. The virus then began to spread across the island but due to COVID-19 lockdowns the spread was difficult to monitor on the ground. With the urgent need to track this epidemic, and in the absence of traditional monitoring, the Babi Hutan Project was launched in April 2021 to gather data on pig sightings using citizen science. Any sightings of bearded pigs were requested via the website, social media and a WhatsApp hotline. Here we bring together the data from this project and other online sources to show how the virus spread across almost the entire island within a one-year period. The speed of spread appeared to increase with time following an exponential model: we estimate an average speed of spread of 0.89 km/day after 100 days since the first observation and at 4.28 km/day after 400 days. Our key recommendations are that existing hunting bans on bearded pigs remain in place; that urgent biosecurity measures should be put in place if outbreaks occur in areas with backyard (domestic) pigs; that surviving pigs are tested for resistance; that the disease dynamics are modelled and that the International Union for Conservation of Nature (IUCN) urgently re-evaluates the bearded pig’s status.